Celiprolol to prevent arterial events in patients with vascular Ehlers-Danlos and neither symptomatic nor silent arterial event. A retrospective cohort study from the French national reference center. (3rd October 2022) - Mazzella, J M; Oehmichen, B; Billon, C; Nicolas, S; Lahlou-Laforet, K; Frank, M; Jeunemaitre, X; Mirault, T
Abstract: Background: Vascular Ehlers-Danlos syndrome (vEDS) is a rare inherited connective tissue disorder, leading to mainly arterial complications, caused by COL3A1 pathogenic variations. Ong et al. (Lancet 2010) showed that the introduction of celiprolol significantly reduced arterial events in a predominantly symptomatic population on arterial level. We reported the benefit of full dose of Celiprolol in longitudinal study to prevent arterial events in Frank et al. (JACC 2019). To our knowledge, there is no data regarding the benefit of celiprolol in patients without any arterial event. Purpose: The aim of this study was to assess the occurrence of arterial events during follow-up in vEDS patients without arterial event. Methods: All patients – probands and relatives – with a pathogenic variation in COL3A1 diagnosed at the Referral Centre for Rare Vascular Diseases since 2001 and at least one arterial tree assessment were included. We then focused on vEDS patients without any arterial event. We retrospectively analyzed the duration of follow-up, the occurrence of arterial events during follow-up, and the introduction and dose of celiprolol, especially at the time of occurrence of an arterial event. Results: Among the 230 patients included, 144 (63%) had at least one symptomatic arterial event, 44 (19%) had only silent arterial event and 67 (29%) had no arterial event at the first arterial tree assessment event. Patients with no arterial event were significantly younger at this visit compared with the two other groups with a median age of 23 vs. 38 and 39 years (silent and symptomatic) (p<0.05). Patients with no arterial event were more frequently relatives (73%) than probands (27%) (p<10–3). Celiprolol was introduced in 48 (72%) of the 67 patients with no arterial event after positive genetic diagnosis disclosure or during one of the outpatient visit. During follow-up, 22 patients had a first arterial event at a median age of 29 years: 16 (33%) were receiving celiprolol and 6 (32%) were not. But the median follow-up duration was 4 years for the 48 treated patients vs. 2 years for the 19 untreated patients (p=0.03). Conclusions: Genetic testing of the relatives of probands with vEDS remains of utmost importance as one quarter presented with symptomatic arterial event and one fifth had silent arterial event at initial arterial tree assessment. For patients with no arterial event, those without celiprolol have a similar incidence of arterial events than those with celiprolol, however their follow-up duration was twice shorter suggesting a higher incidence rate or arterial event in the absence of celiprolol. Funding Acknowledgement: Type of funding sources: None.